Applying a food processing-based classification system to a food guide: A qualitative analysis of the Brazilian experience - Davies, Vanessa Fernandes; Moubarac, Jean-Claude; Medeiros, Kharla Janinny; Jaime, Patricia Constante (Cambridge University Press (CUP), 2018)
Objective The present paper aimed to identify the stakeholders, as well as their arguments and recommendations, in the debate on the application of a food processing-based classification system to the new Brazilian Food Guide. Design Qualitative approach; an analysis was made of documents resulting from the consultation conducted for the development of the new Brazilian Food Guide, which uses the NOVA classification for its dietary recommendations. A thematic matrix was constructed and the resulting themes represented the main points for discussion raised during the consultation. Setting Brazil. Subjects Actors from academia, government and associations/unions/professional bodies/organizations related to the area of nutrition and food security; non-profit institutions linked to consumer interests and civil society organizations; organizations, associations and food unions linked to the food industry; and individuals. Results Four themes were identified: (i) conflicting paradigms; (ii) different perceptions about the role and need of individuals; (iii) we want more from the new food guide; and (iv) a sustainable guide. Conclusions There was extensive participation from different sectors of society. The debate generated by the consultation revealed two main conflicting opinions: a view aligned with the interests of the food industry and a view of healthy eating which serves the interests of the population. The first group was against the adoption of a food processing-based classification system in a public policy such as the new Brazilian Food Guide. The second group, although mostly agreeing with the new food guide, argued that it failed to address some important issues related to the food and nutrition agenda in Brazil.
Keywords: Brazil; Food Guides; Food processing; Public policies